BAUDELAIRE’S SNAPSHOTS OF THE CITY: THE MODERN EXPERIENCE IN FOCUS - Freitas, Viviane Ramos de (fólio - revista de letras, 2018)
This work explores the photographic snapshot aspect of Charles Baudelaire’s city poems in the section “Parisian Scenes” of Flowers of Evil. The text discusses Baudelaire’s contention that photography is art’s mortal enemy, and it draws the attention to the visual impulse of Baudelaire’s urban poetry. The work, then, establishes a dialogic exchange with Walter Benjamin’s analysis of the urban aesthetic experience, which associates Baudelaire’s aesthetics with photography, in their opposition to the auratic aesthetics. Contrary to Benjamin, this work argues for the auratic character of Baudelaire’s poetry. The work focuses on Baudelaire’s activity as poet of the city, an engaged social observer whose poetry, facing the challenge of encompassing the contemporary scene, gradually becomes involved in a critical practice, opening up modern experience to greater scrutiny. In this way, Baudelaire claims the place of the individual within the metropolis and asserts the humanistic character of his poetry